PENGARUH SUPERVISI AKADEMIK DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DENGAN MEDIASI KEPUASAN KERJA (Studi kasus guru SMA dibawah naungan Yayasan Pendidikan Kesatrian Semarang) (Jurnal Mahasiswa Pasca Sarjana, 2014)
The results of this study are the Influence of Academic Supervision , Principal Leadership and Job Satisfaction on Teacher Performance . The research problem in this study are : (1) to examine the Influence of Academic Supervision , Principal Leadership and Job Satisfaction on teacher performance. (2) to test whether job satisfaction mediates Academic Supervision and Leadership Principal of the Teacher Performance. The  samples of this study are 105 teachers of Kesatrian Senior High School under the auspices of the Kesatrian Education Foundation of Semarang The used sampling was census techniques and the used model was multiple regression analysis The results of this study are: (1) the Academic Supervision was prooved in influencing the job satisfaction , (2) the principal's leadership did have positive and significant influence on the teacher satisfaction , (3) Academic Supervision had positive and significant was not proooved influence on teacher performance , (4) the principal's leadership had positive and significant influence on teacher performance , (5) the job satisfaction had positive and significant influence on teacher performance , (6) job satisfaction variable was prooved to have the function as intervening variable on the variable of Academic Supervision on teacher performance , (7) job satisfaction was not proved to have the function as intervening variable on the variable of Principal Leadership on teacher performance. Keywords : academic supervision , the principal leadership , job satisfaction , teacher performance .